2008
DOI: 10.1021/jp805356z
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on Kinetics and Reactivity of the Gas-Phase Addition and H-Abstraction Reactions of Pyridine with Atomic Chlorine

Abstract: Theoretical investigations are carried out on the mechanism, kinetics, and thermochemistry for the reaction between pyridine and atomic chlorine with use of the hybrid density functional model BB1K, BHandHLYP, and the ab initio MP2 method. Both addition to and hydrogen abstraction reaction from all the potential sites are considered. Barrier heights and thermochemistry for all the possible addition and abstraction processes are calculated for the first time. This helps to identify the most reactive reaction ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
3
14
0
1
Order By: Relevance
“…The variation of the CH distances in the pyridine-Cl • system (calculated by the BB1K method) has been discussed in a previous work [16] and it has been shown that the interaction with Cl • mainly affects the CH bond in ortho position of pyridine and that the other CH bond lengths remain almost unchanged. A similar trend is observed in the present work.…”
Section: Nbo Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The variation of the CH distances in the pyridine-Cl • system (calculated by the BB1K method) has been discussed in a previous work [16] and it has been shown that the interaction with Cl • mainly affects the CH bond in ortho position of pyridine and that the other CH bond lengths remain almost unchanged. A similar trend is observed in the present work.…”
Section: Nbo Analysismentioning
confidence: 99%
“…Email: therese.zeegers@chem.kuleuven.be; akchandra@nehu.ac.in pyridine as the dominant reaction channel at low temperature (T < 270 K). It is important to notice that at higher temperature (T > 300 K), H-abstraction becomes important and slowly predominates over the addition channel as the temperature rises [15,16]. The major sources of pyridine derivatives in atmosphere are industrial wastes, coal combustion and tobacco burning.…”
Section: Introductionmentioning
confidence: 99%
“…14 Parveen et al employed hybrid density-functional methods to find that formation of the C 5 H 5 N-Cl adduct with exothermicity of 52 kJ mol −1 is the primary channel at low temperature. 15 Although all three channels for addition of the Cl atom to the ring-carbon sites are predicted to have no barrier, the predicted G values are positive even at 200 K; these ring additions are thus unlikely to contribute to the reaction unless the temperature is much less than 200 K. At high temperature, H-abstraction from the ortho C−H bond becomes feasible. 15 Zhao et al investigated the kinetics of the gaseous reaction Cl + C 5 H 5 N using laser flash photolysis and resonance fluorescence and found that H-abstraction is the dominant channel above 299 K, whereas in the temperature range 216−270 K the formation of an adduct is the major reaction channel as indicated by a pressure-dependent rate coefficient much greater than that for H-abstraction.…”
Section: Introductionmentioning
confidence: 99%
“…This experimental value of H • 298 is consistent with that predicted quantum-chemically for the formation of a planar adduct with a N−Cl σ -bond. 13,15 The matrix isolation technique is an excellent method to investigate IR spectra of reactive intermediates. 17,18 Because of the cage effect that inhibits the Cl from escaping from the original cage upon photolysis of its precursor such as Cl 2 , photolytic reactions of Cl atom in noble-gas matrices are ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…21 Similarly, the temperature dependence of the gas-phase reaction of Cl atoms with propene and 1-butene was studied by FTIR within the range of ambient temperatures (285 o T o 313 K). 25 At lower temperature, the primary reaction channel is addition of Cl to the pyridine N-atom forming an adduct (C 5 H 5 N-Cl) through a weak N-Cl bond as the D r G values for reactions with the ring hydrogens remains positive. Calculations at the B3LYP/RCEP60 VDZ level of theory have recently been used to study the chlorine oxidation of mercury as a model for mercury speciation in the quench zone of flue gases.…”
mentioning
confidence: 99%